Cutaneous side-effects during therapy of melanoma by vemurafenib - Anna Ankudowicz; Urszula Brzezicka-Ciach; Bożena Wenska (Termedia Publishing House, 2015)
Introduction. Vemurafenib is a selective inhibitor of serine-threonine kinase BRAF used in the treatment of advanced melanoma with BRAF mutation. Effectiveness of this drug was confirmed in a large clinical trial, which led to the increase of its usage. During treatment with vemurafenib, particular attention should be paid to the numerous side effects, including those concerning the skin. Vemurafenib is highly toxic to the skin. Skin lesions occurring during the treatment of melanoma with this medicament can be divided into: early (observed 3 to 6 weeks after beginning treatment), late (observed 6 weeks after beginning treatment) and hypersensitivity reactions to vemurafenib. Objective. Presentation of vemurafenib toxic effects on the skin and side effects that can be caused by this drug. Case report. We present a 58-year-old woman with metastatic melanoma who was treated with vemurafenib. During the course of therapy, numerous adverse reactions, including inflammatory tumors, emergence of a number of melanocytic naevi, skin horns, alopecia, hyperkeratosis of the palms and soles, and palmar erythrodysesthesia were observed. She was treated with anti-inflammatory drugs, an antibiotic, circulation-improving preparations and local moisturizing and keratolytic treatment. The patient remains under the care of oncologists and dermatologists. Conclusions. The new generation anti-cancer drugs bring hope for a cure or prolongation of life, but can also significantly reduce the quality of life by inducing both general and local adverse side effects. Oncological patients should also be taken care of by dermatologists.